A Short narrative and justification of the proceedings of the committee appointed by the Adventurers, to prosecute the discovery of the passage to the western ocean of America [electronic resource] : and to open and extend the trade, and settle the countries beyond Hudson's Bay, with an appology for their postponing at present their intended application to Parliament : to which are annexed, the report and petitions referred to in the narrative, and the papers prepared to be delivered to the Lords and Commons, upon presenting the petition, as the foundation for a parliamentary enquiry, and the facts they were prepared to support : now laid before the publick, for their future consideration. - Dobbs, Arthur, 1689-1765. (London : Printed for J. Robinson ., 1749)
Sometimes attributed to Arthur Dobbs--National Union Catalog pre-1956 imprints. Electronic reproduction. Mode of access: Internet. 44